2019
DOI: 10.1177/0269216319840275
|View full text |Cite
|
Sign up to set email alerts
|

Good end-of-life care in nursing home according to the family carers’ perspective: A systematic review of qualitative findings

Abstract: Background: Nursing homes are becoming a common site where delivering end-of-life care for older adults. They often represent the junction between the curative and the palliative phase. Aim: To identify the elements that nursing home residents’ family carers perceive as good end-of-life care and develop a conceptual model of good end-of-life care according to the family perspective. Design: Systematic review (PROSPERO no. 95581) with meta-aggregation method. Data Sources: Five electronic databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 72 publications
7
81
0
4
Order By: Relevance
“…Interviews after a year of SHARE indicated that more communication and collaboration between Hospice and RAC facilities led to positive responses by families regarding the quality of care for their relatives (4,8). Re ecting previous research (8) a poor relationship between hospice and RAC facilities was a source of family concern before SHARE.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interviews after a year of SHARE indicated that more communication and collaboration between Hospice and RAC facilities led to positive responses by families regarding the quality of care for their relatives (4,8). Re ecting previous research (8) a poor relationship between hospice and RAC facilities was a source of family concern before SHARE.…”
Section: Discussionmentioning
confidence: 71%
“…Palliative care is de ned as care for a person with a life-limiting illness that aims to optimise the quality of life for the person, as well as support their whānau (family) caregivers both during illness and after death (2). Palliative care is one component of an overall health care plan and may be more needed than a purely treatment focused plan at the end-of-life (8). Palliative care is delivered by both generalists as a part of standard clinical practice by any healthcare professional and by specialist palliative care professionals who have undergone specialist training in palliative care (2).…”
Section: Introductionmentioning
confidence: 99%
“…Eight interviews with bereaved family members (7 women, 1 man) were conducted before SHARE. Interviewees were most often between the ages of 70-79 and the majority [8] identified as NZ European and reported Christianity as their religion [4]. Five of the decedent residents had diagnoses of dementia (Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…Palliative care is defined as care for a person with a life-limiting illness that aims to optimise the quality of life for the person, as well as support their whānau (family) caregivers both during illness and after death [2]. Palliative care is one component of an overall health care plan and may be more needed than a purely treatment focused plan at the end-of-life [8]. Palliative care is delivered by both generalists as a part of standard clinical practice by any healthcare professional and by specialist palliative care professionals who have undergone specialist training in palliative care [2].…”
Section: Introductionmentioning
confidence: 99%
“…Spirituality at the end of life is important to patients,4 5 and family carers,6 and has a positive association with patients’ quality of life, physical health and social well-being 2 7. Patients report being comfortable with healthcare providers inquiring about spiritual needs8; however, spiritual and social issues are discussed less often by healthcare providers than other end-of-life issues such as physical symptoms 9.…”
Section: Introductionmentioning
confidence: 99%